Phosphatase and Tensin Homolog Hamartoma Tumor Syndrome: A Case Report. Issue 1 (1st February 2016) - Holt, Amon E.; Ferguson, Brett L.; Gibson, Tanya M.; Satheesh, Keerthana M.; Cobb, Charles M.
Abstract : Introduction: Phosphatase and tensin homolog (PTEN) hamartoma tumor syndrome (PHTS) may manifest as one of four distinctive disorders: 1) Cowden syndrome; 2) Bannayan‐Riley‐Ruvalcaba syndrome; 3) Proteus syndrome; or 4) Proteus‐like syndrome. Clinical features of PHTS commonly include multiple benign hamartomas of the skin and mucous membranes as well as macrocephaly. Despite the benign nature of the characteristic lesions, patients diagnosed with PHTS are at increased risk of certain cancers, most notably carcinomas of the breast, thyroid, and endometrium. Case Presentation: A 28‐year‐old African‐American female presented with generalized gingival overgrowth that involved the palate, gingival margins, and retromolar areas. The dorsal tongue also exhibited a generalized tissue hyperplasia. Based on clinical presentation, biopsies were performed for histology and genetic testing. Although histology revealed non‐specific fibroepithelial hyperplasia, genetic testing revealed a novel heterozygous mutation of the PTEN gene (c.158_164dupTAGTAAG), believed to result in premature termination of the protein. The patient did not exhibit macrocephaly or extraoral skin lesions and did not have any obvious cognitive deficit. Conclusions: This presentation of a Cowden syndrome‐like scenario demonstrates that intraoral lesions may be the first symptom leading to a diagnosis of PHTS. Furthermore, the case shows that communication with and referral from the general dentist to specialists (e.g., oral pathologist, oral surgeon, or periodontist) can facilitate the establishment of a definitive diagnosis and allow for preventive screening and genetic counseling to aid in the treatment of secondary diseases, most notably associated cancers.